Sleep practices implemented by team sport coaches and sports science support staff: A potential avenue to improve athlete sleep? - Miles, K. H.; Clark, B.; Fowler, P. M.; Miller, J.; Pumpa, K. L. (Journal of Science and Medicine in Sport, 2019)
Objectives: The primary aims of the present study were to assess the sleep hygiene knowledge of high performance team sport coaches and sports science support staff; the sleep practices these individuals implement with athletes; and the barriers to the more frequent use of these practices. Design: Cross-sectional observational study. Methods: A sample of 86 Australian coaches and sports science support staff working within high performance team sport volunteered to complete a four-part questionnaire, including the Sleep Beliefs Survey used to assess sleep hygiene knowledge. Results: Overall sleep hygiene knowledge was adequate (15.3 ± 2.9, score range 0-20; mean ± SD), however knowledge of sleep-wake cycle behaviours (score 4.9 ± 1.6 out of 7) and thoughts and attitudes about sleep (3.6 ± 1.0 out of 5) were inadequate. Over half (56%) of coaches and support staff had monitored athlete sleep, while 43% had promoted sleep hygiene. Lack of resources (response range 44-60%) and knowledge (16-41%) were the two main barriers to the implementation of sleep monitoring and sleep hygiene practices. Conclusions: Team sport coaches and sports science support staff have adequate overall sleep hygiene knowledge, yet some specific areas (e.g. sleep-wake cycle behaviours) warrant improvement. There appear to be limited sleep practices implemented with athletes, particularly regarding the promotion of sleep hygiene. The development of educational sleep resources for coaches and support staff to implement with athletes may help address the identified barriers and improve sleep knowledge.